Edukasi Dan Pendampingan Wajib Pajak Masyarakat Pedesaan : (Study Desa Lontos Kecamatan Luwuk Timur) - Irna Harpin Baso; Putri Maryati Ahmad; Moh Ikbal Lalusu; Aditia S Towenso; Falimu Falimu; Fadli Sandewa (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
The role of education and assistance to taxpayers in the context of Lontos Village. Through a scientific approach, this research highlights the importance of education and assistance as an effort to increase taxpayers' understanding and awareness of tax obligations. The implementation of this service aims to provide education and assistance as well as provide understanding and awareness to the public as taxpayers regarding the importance of paying taxes in Lontos Village, East Luwuk District. The methods used in implementing the service are direct observation, interviews, and carrying out service activities related to tax education in Lontos Village. The results of the service implementation are that structured and targeted education and assistance can make a positive contribution in increasing taxpayer compliance and strengthening the relationship between taxpayers and the village government as the authority in tax collection. The implication of these findings is the need to increase education and mentoring programs on an ongoing basis to support tax awareness and strengthen the tax system at the local level. The service carried out provides valuable insight for related parties in designing effective strategies to support tax compliance in Lontos Village, East Luwuk District, Banggai Regency and may also be applied in a broader taxation context.